Varicocele and non-obstructive azoospermia – where to start? - A. Yu. Popova; S. I. Gamidov; R. I. Ovchinnikov; N. P. Naumov; N. G. Gasanov (Андрология и генитальная хирургия, 2018)
Background. Male etiology is responsible for nearly half of cases of infertility. Frequency of azoospermia in infertile men reaches 30 %; varicocele is diagnosed in almost 40 % of the patients. Varicocele- associated infertility has traditionally been considered an indication  for surgical treatment. At the same time, the main method of sperm  retrieval in azoospermia is testicular biopsy (testicular sperm  extraction, TESE).Objective: to assess the efficacy of surgical treatment in patients with non-obstructive azoospermia (NOA) and varicocele.Materials and methods. The study included 327 patients with NOA and varicocele aged between 22 and 48 years treated in the Department of Andrology and Urology at the V. I. Kulakov National  Medical Research Center of Obstetrics, Gynecology, and Perinatology  in 2012– 2016. Study participants were divided into two comparable  groups. Patients in the first group underwent microsurgical  varicocelectomy (Marmara procedure) on the first stage and  testicular biopsy (micro-TESE) on the second stage. Patients in the  second group underwent micro-TESE with no surgical correction of varicocele prior to it.Results. In the first group, the appearance of spermatozoa in ejaculate was observed in 84 (44.4 %) patients 6 month post microsurgical varicocelectomy. Upon micro-TESE, spermatozoa  suitable for use in assisted reproductive technologies were obtained  in 60 (56.7 %) men. Treatment was effective in 144 (76.2 %)  patients from the first group. In the second group, spermatozoa  were retrieved in 66 (47.8 %) men upon micro-TESE.Conclusion. Microsurgical varicocelectomy increases treatment efficacy in males with NOA and varicocele. In the absence of severe degeneration of the seminiferous epithelium, 72.6 % of patients had  the opportunity of becoming a genetic parent, avoiding in some  cases testicular biopsy.